Physical treatments to enhance nutritive value of palm kernel expeller in finisher diet for broilers - Shakirin, Faridah Hanim (2020)
Annual importation of livestock feed in Malaysia amounting to RM11bil, with corn and soybeans accounted for the bulk of the imported feed costs. Depending on the price of ingredients, by weight, corn makes up 60-65% and soybean 26-32% of the poultry feed in finisher diet. Thus, Malaysia has to cut back on the importation of poultry feed ingredients, particularly corn and soybean, to ensure long term sustainability of the industry. Higher usage of palm kernel expeller (PKE) in poultry feed could reduce the country dependency on imported feed. Effort to use PKE as feed component in broilers has been constrained by its high fiber content. Biological treatments are the most common methods used to improve the nutritive value of PKE but they achieved limited success. Physical treatments which have been proven to be effective in enhancing the nutritive value of other feed ingredients, but not well tested in PKE, is the theme of this thesis. Several physical treatments; including grinding, sieving and extrusion, were evaluated for their effects on chemical composition, particularly crude fiber (CF) reduction, and alteration of hydration properties of PKE. From the results, both extrusion and sieving (but not grinding) significantly (p<0.05) reduced CF by 1.3 and 1.2 folds, respectively, as compared to the untreated PKE. Also, extrusion significantly (p<0.05) increased total reducing sugar, soluble protein and starch contents by 5, 1 and 8.5 times, respectively, as compared to the control; while sieving resulted in no increase (p>0.05) in reducing sugar, 1.5 folds increment in soluble protein, however, sieving increased (p<0.05) swelling capacity, and water retention capacity by 1.3 and 1.2 folds, respectively. In the second experiment, 64 male Cobb 500 chicks were used to determine the apparent metabolizable energy (AME), protein and amino acid digestibility of the sieved and extruded PKE prepared according to the protocols of the first experiment. Results showed that extrusion significantly (p<0.05) increased the AME of PKE from 13.21 to 14.04 MJ/kg, while sieving has no effect on AME of PKE. Both, extrusion and sieving significantly (p<0.05) enhanced protein digestibility by 1.32 and 1.39 folds, respectively. The primary objective of the feeding trial was to compare the production parameters of broiler fed increasing levels (10, 20 and 30%) of untreated and extruded PKE to determine the maximum inclusion level of PKE in the finisher diet. The trial focused on finisher-diet phase in which diets were formulated to contain up to 30% PKE. Changes in the intestinal morphology and nutrient assimilation in the intestine using the expressions of transporter genes were also monitored. Results showed that birds fed 30% extruded PKE (30EPKE) sustained similar weight gain (WG) and feed conversion ratio (FCR) while those fed 30% untreated PKE (30PKE) had poorer WG and FCR (p<0.05) as compared to those fed 10% PKE. The above result indicated that extruded PKE (30EPKE) can be included up to 30% in finisher broiler diet. The better WG and FCR of birds fed 30EPKE (p<0.05) over 30PKE were accompanied by up-regulation (p<0.05) of sugar (GLUT2, SGLT5) and amino acid (PepT1 and EAAT3) transporters in the former group. Increased villus height and crypt depth (p<0.05) were observed in birds fed high (30%) PKE and mainly at the jejunum and ileum sections. Feeding up to 30% PKE (extruded or untreated) did not significantly (p>0.05) altered the accumulation of minerals in the liver as there is no changes on the liver and kidney morphology. This indicated that the health and wellbeing of the birds were not compromised. It is concluded that extruded PKE can be included up to 30% in finisher-diet to sustain the normal growth and FCR without affecting the overall health and wellbeing in broilers.